Pemantauan Dan Pengendalian Pintu Air Berbasis Komunikasi Radio Full Duplex Dengan Algoritma Decision Tree - Kurniawan, Asep; Hermawan, Indra; Agustin, Maria (MULTINETICS, 2023)
Provision, management and distribution of water on agricultural land is one of the important factors that affect the quantity and quality of agricultural products. An irrigation canal technology is needed that is able to flow through all agricultural land according to the water needs of each land. Smart irrigation systems can be a solution to this problem. The smart irrigation technology that was previously developed has several limitations such as the length of time data transmission takes to reach the client, sensor devices in the field must take turns sending data and receiving data resulting in data not being sent or not being read properly, besides that the system that has been developed previously depends on to one factor, namely the water level to determine the degree of openness of the floodgates. In this research a fast sensor to cloud communication system is designed using websocket technology. This system is also designed to send and receive data simultaneously using full duplect communication technology. As well as using artificial intelligence with the decision tree algorithm to regulate the openness of the floodgates based on the water requirement for the rice fields, the water level in the irrigation canals and the speed of the water flow. This research produced a prototype of an intelligent irrigation system that can send data to clients with an average time of 417ms, the system is also able to handle 500 clients that are connected directly to the server. The system can also send and receive data simultaneously with a difference in time when data is received at the sensor node or at the central node which can reach 0ms. This prototype also succeeded in making an artificial intelligence system that is accurate, fast and real-life. This artificial intelligence can handle 500 requests simultaneously with an execution time of 544ms.